Project-Based Learning Based on the Local Wisdom of the Malind Tribe: Learning Innovation to Realize Future Learning in Border Schools - Ni Nyoman Rediani; Herrio Tekdi Nainggolan; Bernadetha Rizki Kaize; Yusri (International Journal of Community Service Learning, 2026)
The low ability of teachers to determine projects in PjBL learning and the lack of understanding of teachers related to PjBL learning. This community service is carried out to increase teacher capacity in designing and implementing context-based project-based learning (PjBL) aligned with the Independent Curriculum. This community service activity was carried out at YPPK St. Fransiskus Xaverius Elementary School. The number of training participants was 20 people. The activity was carried out through several stages: preparation, training, workshops, and mentoring. In the preparation stage, the implementation team identified teacher needs and problems through field surveys and the preparation of activity administration tools. The survey results showed that most teachers experienced difficulties in designing learning projects and did not understand the basic syntax of the PjBL model. The training and workshop stages focused on strengthening teachers' conceptual understanding and practical skills in developing project-based teaching tools, with the result that around 80% of participants were able to develop learning tools that aligned with learning outcomes and integrated local cultural values of the Malind Tribe. Meanwhile, the mentoring phase significantly improved the quality of teaching materials and teachers' confidence in implementing PjBL in the classroom. The results of this activity demonstrate that training and mentoring are crucial for improving teachers' knowledge, skills, and productivity in border areas.